PENGGUNAAN MEDIA PESAN BERANTAI UNTUK MENINGKATKAN PENGENALAN PEKERJAAN PENDIDIKAN ANAK USIA DINI (PAUD) - Tri Ani; Asri Neli Putri (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the use of chain messages as a medium to enhance the introduction of professions in Early Childhood Education (PAUD) and its implications for PAUD educator competency standards. The method employed is a qualitative literature review with a descriptive-analytical approach. Data were collected from various relevant sources, including scientific journals, books, and government regulations, and analyzed using content analysis. The results indicate that chain message games are effective in introducing professions because they involve visual stimulation, verbal communication, and multisensory activities that align with brain-based learning principles (Suyadi, 2020). The implementation of this method carries significant implications for PAUD teacher competencies, including pedagogical competency in designing brain-friendly games, professional competency in integrating knowledge from child development, communication, and neuroscience, social competency in building healthy communication ecosystems, and personality competency in creating a fun and non-stressful learning environment. The study concludes that chain message media is an innovative and relevant solution to introduce professions to young children while also strengthening the professional image of PAUD educators.